Successful Implementation for Thailand as an emerging donor for infrastructure development in GMS - Shuaytong, Onramon; Chotchakornpant, Kasemsarn (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The objectives of this study were to: (1) study the factors affecting the success of financial aid under infrastructure development projects in the Greater Mekong Sub-region (GMS), and (2) propose a model for project implementation success. This study is the qualitative research by using three research methods in gathering data, consisted of document analysis, semi-structured interviews, and non-participant observation. The semi-structured interviews were conducted with 34 key informants comprised of 9 key informants from Thai government agencies, 6 key informants from local administrations, 15 key informants representing the local people, and 4 key informants from Laos People’s Democratic Republic, Kingdom of Cambodia, and Republic of the Union of Myanmar. All key informants have involved directly in road construction projects. The study findings from content analysis revealed that government agents defined success at the outcome level, which consisted of improving quality of life, Sub-region economic development, and fostering partnerships with neighboring countries. On the other hand, the local administrations and local people considered success at the output level, which consisted of reducing travel time and facilitating cross-border trade. The factors affecting the success of financial aid under infrastructure development projects in GMS consisted of 5 factors: (1) standards and objectives of policy requirements, (2) involvement and participation among stakeholders, (3) organization configuration management, (4) the social and political atmosphere, and (5) harmonization and coordination among stakeholders. The project implementation success model is presented consistent with evidence found in stakeholders considered success at the different level which effecting to various success factors. For the policy recommendations, the government sector should promote constructive relationships with neighboring countries and be aware of the best interests of neighboring countries. Moreover, the government sector should develop the foundation of legal, regulations as well as standards agreements under GMS along with hard infrastructure development.